Design, synthesis, and biological evaluation of potent 1, 2, 3, 4-tetrahydroisoquinoline derivatives as anticancer agents targeting NF-κB signaling pathway. (15th September 2021) - Sim, Seongrak; Lee, Sumi; Ko, Seungyun; Phuong Bui, Bich; Linh Nguyen, Phuong; Cho, Jungsook; Lee, Kiho; Kang, Jong-Soon; Jung, Jae-Kyung; Lee, Heesoon
Graphical abstract: Highlights: A new series of 1, 2, 3, 4-tetrahydroisoquinoline derivatives were designed based on the chemical structures of previous potent NF-κB inhibitors. Thirteen isoquinoline and twenty 1, 2, 3, 4-tetrahydroisoquinoline compounds were synthesized. Compound 5d presented the most promising anti-proliferative activity against six human cancer cell lines. Compound 5d blocked NF-κB nuclear translocation step in LPS-stimulated MDA-MB-231 cells. Abstract: The multifunctional transcription factor, nuclear factor-κB (NF-κB), is broadly involved in multiple human diseases, such as cancer and chronic inflammation, through abnormal modulations of the NF-κB signaling cascades. In patients with several types of cancer diseases, NF-κB is excessively activated, which could result in the stimulation of proliferation and/or suppression of apoptosis. Herein, we present a new series of 1, 2, 3, 4-tetrahydroisoquinoline derivatives with good anticancer activities against various human cancer cell lines, which are rationally designed based on our novel NF-κB inhibitors. The SAR studies demonstrated that compound 5d with a methoxy group at the R 3 position exhibits the most anti-proliferative activity with GI50 values, ranging 1.591 to 2.281 μM. Similar to KL-1156, the compound 5d (HSR1304) blocked NF-κB nuclear translocation step in LPS-stimulated MDA-MB-231 cells, probably leading to cytotoxic potency against tumor cells. Together with known potent NF-κB inhibitors containing diverse core heterocyclic moieties, the 1, 2, 3, 4-tetrahydroisoquinoline derivatives can provide structural diversity, enhancing a potential for the development of a novel class of anticancer drugs.